Systemic lupus erythematosus in a 20-year-old woman: a case report - Manikasari, Ayu S.; Tedja, I. Gusti Ayu Wiradari; Prianggandanni, Made A. V. (International Journal of Advances in Medicine, 2025)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease affecting multiple organ systems. It predominantly occurs in women of reproductive age, with a global prevalence ranging from approximately 20 to 150 cases per 100,000 individuals. The diagnosis of SLE can be supported by antinuclear antibody (ANA) testing, which includes an initial screening with immunofluorescence ANA (ANA-IF), followed by an ANA profile to identify specific autoantibodies. A 20-year-old female presented with complaints of easy fatigue, fever, joint pain, and hair loss. Laboratory investigations revealed anemia. Immunological testing demonstrated a positive ANA-IF result with a titer of 1:1000 and a delicate speckled pattern, meeting the EULAR/ACR criteria that consider a positive ANA-IF titer ≥1:80. Based on these clinical and laboratory findings, the patient was diagnosed with SLE and commenced on corticosteroid therapy. Subsequent follow-up showed clinical improvement. This case highlights the importance of careful interpretation of ANA-IF titers and patterns for the early detection of SLE. Additionally, specific autoantibody profiling remains essential to support a more precise diagnosis.